2018
DOI: 10.1111/1365-2745.13079
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen recycling in coupled green and brown food webs: Weak effects of herbivory and detritivory when nitrogen passes through soil

Abstract: The study of coupled green and brown food webs has improved our ability to understand how nutrient cycling and plant communities respond to perturbations. Yet, it is still difficult to predict how rapidly and consistently changes in one food web propagate to the other. An area of particular uncertainty is the response of plants to the changes in leaf litter nitrogen release caused by herbivores and detritivores. We combined a field experiment and theoretical analysis to assess how herbivory, fertilization, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…S2 and S3). Our results are therefore consistent with empirical assessments that brown food web dynamics may play an underappreciated role in green-brown coupled N cycling (Holtkamp et al 2011, Kostenko et al 2012, Laungani et al 2012, Buchkowski et al 2018.…”
Section: Discussionsupporting
confidence: 90%
“…S2 and S3). Our results are therefore consistent with empirical assessments that brown food web dynamics may play an underappreciated role in green-brown coupled N cycling (Holtkamp et al 2011, Kostenko et al 2012, Laungani et al 2012, Buchkowski et al 2018.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, predator effects will depend on whether they are mediated by herbivores in the plant-based food chain, by detritivores in the detritusbased food chain, or by a cascading chain of effects among both prey groups. For example, predator-prey interactions can determine herbivore effects on plant biomass and chemistry via changes in litter quality, thereby altering detritivore impacts on soil nutrient availability (Buchkowski et al, 2019). Incorporating such a food-web framework will likely uncover important predator effects on terrestrial nutrient cycling.…”
Section: Discussionmentioning
confidence: 99%
“…These drastic changes in microbial activity following litter consumption by G. marginata raise an important issue: the impact of soil macro-detritivores on the coupling between above-and belowground components of ecosystems. Only few studies that have hitherto examined the influence of aboveground processes on plant litter decomposition considered the role of macroarthropods (Buchkowski, Schmitz & Bradford, 2019). For example, studies in fine-mesh litter bags excluding macrofauna have shown that intraspecific changes in litter quality in response to herbivory affect litter decomposition rates (Olofsson & Oksanen, 2002;Semmartin & Ghersa, 2006;Wang et al, 2018).…”
Section: Potential Disruption Of Aboveground-belowground Linkages By Macroarthropodsmentioning
confidence: 99%